2009
DOI: 10.1183/09031936.00133608
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient treatment and early discharge of symptomatic pulmonary embolism: a systematic review

Abstract: The published literature regarding the safety of outpatient treatment of symptomatic pulmonary embolism (PE) was systematically summarised.A literature search was performed using the PubMed and EMBASE databases. Studies in which patients had symptomatic PE and the antithrombotic treatment was administered completely at home or the patients were discharged early were selected. A scoring system was used to divide studies into three quality categories. Short-and long-term outcomes were extracted: all-cause mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 48 publications
1
35
0
2
Order By: Relevance
“…Two systematic reviews suggested that patients with acute PE treated as outpatients had low incidences of major bleeding, recurrent venous thromboembolism (VTE), and mortality [14,15]. However the quality of the included studies was low and subsequent and recent larger observational studies and randomized control trials were not included [8,11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews suggested that patients with acute PE treated as outpatients had low incidences of major bleeding, recurrent venous thromboembolism (VTE), and mortality [14,15]. However the quality of the included studies was low and subsequent and recent larger observational studies and randomized control trials were not included [8,11,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews summarised the results of a few small observational studies on outpatient treatment in patients with PE [2,3]. These reviews concluded that although the evidence is not of high quality, it indicates that certain subgroups of patients with PE could be eligible for outpatient treatment.…”
mentioning
confidence: 99%
“…10 Both version of PESI score, original and simplified, have been used as prognostic model for identifying low risk patients candidate for home treatment. [11][12][13] Despite this background, literature evidence reporting on which is the best prognosticator for adverse outcome in patients suffering for acute PE in real world lacks. Therefore, the aim of the present study was to compare and combine the predictive values of 2008 European Society of Cardiology prognostic model (ESC) and simplified PESI score (sPESI) as prognosticator for inhospital mortality and fatal and/or major bleedings.…”
Section: Introductionmentioning
confidence: 99%